2012
DOI: 10.1161/atvbaha.112.248609
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Adipocyte Fatty Acid-Binding Protein Levels and Cardiovascular Morbidity and Mortality in Patients With Coronary Heart Disease

Abstract: Objective— Adipocyte fatty acid-binding protein (A-FABP) abundantly expressed in mature adipocytes and activated macrophages has dramatic effects on atherosclerosis in mice. Whether this pathophysiological role of A-FABP may also apply to atherosclerotic disease in humans is still unknown. This study investigated associations among serum A-FABP levels, cardiovascular risk factors, and long-term secondary cardiovascular disease (CVD) outcome in patients with coronary heart disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 30 publications
7
86
0
1
Order By: Relevance
“…In addition, prospective studies have shown that FABP4 can predict the development of metabolic syndrome and type 2 diabetes . Since metabolic syndrome and insulin resistance are closely linked with CVD, a strong association between circulating FABP4 levels and this pathology has also been proposed , Miyoshi et al 2010, Bao et al 2011, von Eynatten et al 2012, Fuseya et al 2014 (Fig. 2).…”
Section: Fabp4 As a Cardiometabolic Predictor For Cvdmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, prospective studies have shown that FABP4 can predict the development of metabolic syndrome and type 2 diabetes . Since metabolic syndrome and insulin resistance are closely linked with CVD, a strong association between circulating FABP4 levels and this pathology has also been proposed , Miyoshi et al 2010, Bao et al 2011, von Eynatten et al 2012, Fuseya et al 2014 (Fig. 2).…”
Section: Fabp4 As a Cardiometabolic Predictor For Cvdmentioning
confidence: 92%
“…Recently, FABP4 has been proposed as a prognostic biomarker in patients with acute coronary syndrome (Reiser et al 2015). In addition, FABP4 is an important predictor of cardiovascular outcomes in patients with either coronary heart disease or acute ischaemic stroke (Holm et al 2011, von Eynatten et al 2012. Along with its potential role Endocrine and paracrine effects of FABP4 linked to obesity-induced HF and CVD.…”
Section: Fabp4 As a Cardiometabolic Predictor For Cvdmentioning
confidence: 99%
“…AFABP levels positively correlate with metabolic and inflammatory cardiovascular risk factors, which include atherogenic dyslipidemia, hyperglycemia, hypertension and also some laboratory markers of inflammation (s-CRP and IL-6). For people with pre-existing coronary heart disease, a significantly higher concentration of AFABP4 predicted increased risk of cardiovascular death, nonfatal myocardial infarction or stroke 48 . Expression of the adipocyte fatty-acid-binding protein (FABP4) gene in macrophages can be induced by oxidized LDL cholesterol and decreased by administration of lipid-lowering drugs (statins), which inhibit cholesterol synthesis 49 .…”
Section: Adipocyte Fatty-acid-binding Protein (A-fabp)mentioning
confidence: 99%
“…In a recent study, circulating A-FABP levels and CV morbidity and mortality in patients with coronary heart disease were examined [32]. This study included a ten-year follow-up with > 200 major CV events and reported that circulating A-FABP levels are associated with long-term prognosis in patients with coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%